INCREASING LITERACY OF ISLAMIC PRODUCTS IN THE BEKARE COMMUNITY: PENINGKATAN LITERASI PRODUK KEUANGAN SYARIAH PADA MASYARAKAT BEKARE - Romadhoni, Cindy Fatika; Sa’adah, Cindy Kaela; Fitriah, Ika; Ulya, Husna Ni’matul (Khidmatuna: Jurnal Pengabdian Masyarakat, 2024)
The socialization activity which was carried out with the theme of increasing literacy in Islamic financial products was carried out on July 20, 2023 at the Bekare village hall, Bungkal District. The purpose of this activity is to expand public knowledge about Islamic banking, change people's mindset in managing finances, and introduce sharia-based financing products so that it is hoped that the public can understand, choose and use sharia financial products and services according to their needs. The method of collecting data from activities carried out using descriptive quantitative data using a questionnaire using a Likert Scale approach consisting of S (Agree), KS (Disagree), TS (Disagree) during the pre-test and post-test with 10 questions. From the results of the pre-test data above, it can be concluded that the 22 participants each understood the importance of literacy in Islamic financial products which included question 1 (73%), question 2 (82%), question 3 (95%), question 4 (23 %), question 5 (59%), question 6 (50%), question 7(68%), question 8 (36%), question 9 (86%), and question 10 (77%). From the results of the post-test data above, it can be concluded that the 22 participants each understood the importance of literacy in Islamic financial products which included question 1 (100%), question 2 (100%), question 3 (95%), question 4 (91%), question 5 (95%), question 6 (95%), question 7 (9%), question 8 (86%), question 9 (95%), and question 10 (95%). It can be concluded that this socialization activity using the lecture method and question and answer session has succeeded in significantly increasing participants' understanding of Islamic financial product literacy, although there is still potential to increase understanding in certain aspects.